Entrepreneurship Education as a Vehicle for K-12 Inclusion: A Case with Boys & Girls Clubs of America. (7th July 2023) - Slatten, Lise Anne; Stewart, Geoffrey; Lanier, Patricia; Credo, Keith R.; Bendickson, Joshua S.
This learning innovation offers a model by which university faculty can increase community engagement, provide greater opportunities to under-served populations, and advance inclusive programming in entrepreneurship education. We present a learning innovation to enhance working with local K-12 focused nonprofit organizations to positively influence individuals, communities, and local entrepreneurship ecosystems.